New species, new record, and key to the species of Rhagovelia in the robusta group (Hemiptera: Heteroptera: Veliidae) from Venezuela - Magalhães, Oséias Martins; Reduciendo-Klementová, Barbora; Svitok, Marek; Moreira, Felipe Ferraz Figueiredo (Zootaxa, 2019)
Rhagovelia kmenti Magalhães & Moreira, sp. nov. is described, illustrated, and compared with congeners. The new species belongs to the robusta group and its males can be distinguished from group congeners by the dark-brown general coloration, the armature of the hind trochanter, femur, and tibia, and by the distinctive shape of the paramere. In addition, Rhagovelia brunae Magalhães & Moreira, 2016 is newly recorded from Venezuela and a key to the species of the robusta group from the country is presented.